Right upper lobectomy for lung cancer with a displaced right bronchus: Two case reports. (2022) - Hara, Kantaro; Matsuda, Yumi; Furukawa, Nao; Miyamoto, Hikaru; Kimura, Takuya; Okabe, Kazunori
Abstract: Case 1 describe a 73-year-old man with an abnormal opacity in the upper lobe of the right lung on chest computed tomography (CT), which was done during the postoperative follow-up for bile duct cancer. The chest CT scan showed a ground glass nodule (GGN) measuring 1.0 cm and another one measuring 0.6 cm of the right lung. Case 2 involved a 79-year-old woman with an abnormal opacity in the upper lobe of the right lung on a chest CT that was obtained after she fell down the stairs. The CT scan showed a solid mass measuring 3.0 cm in the right upper lung. Both the patients underwent bronchoscopy before surgery and showed bronchial branching abnormalities. The surgical procedures could be performed accurately since sufficient information had been acquired pre-operatively and they diagnosed lung cancer. Both the patients were able to undergo radical surgery for lung cancer and are currently doing well with no postoperative complications or recurrence of lung cancer.